INDUSTRY NEED FOR AB ENGLISH LANGUAGE PRACTICUM TRAINEES - Bellena, Gemma B. (PEOPLE: International Journal of Social Sciences, 2016)
This paper looks into the industry need for AB English Language Practicum trainees, which in a way is seen to be an indicator of the need for future AB English graduates. Language Practicum (LP) refers to the On-the-Job Training (OJT) for Bachelor of Arts in English of the College of Arts and Letters, Bicol University. More practically, the study enumerates job descriptions in the market fit for trainees and lists down competency requirements from them. It used as checklist job descriptions/titles identified in Hermosa, et al.’s (2014) as top job descriptions available in the market for Language Practicum trainees. The study is anchored on the questions-oriented model of evaluation, or more appropriately quasi-evaluation. It began with questions to give evidence on the worth and merit of the Language Practicum and its continued place in the AB English curriculum. For its findings, the five top jobs handled by the trainees include those of: administrative officer, information officer, customer service representative, clerk and technical/speech writer. By their ranks, the competency requirements are: collaboration and teamwork; critical thinking, problem solving; life and career; ICT literacy; communication; information literacy; personal and social responsibility; citizenship/civic literacy; creativity and innovation; and environmental awareness. It is therefore concluded that AB English students are better suited for work related to specific communication purpose, that of sharing information within a business or organization. The recommendations are, that: (a) AB English curriculum be geared more to core competencies related to the business world, particularly on corporate/organizational communication; (b) Language Practicum insists that sponsoring organizations train students to hone these competencies more, and not solely to provide extra manpower to do menial tasks which are part of the job description.